(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Since the industrial revolution, environmental changes have begun to affect both human life and natural systems such as weather patterns. The increased usage of fossil fuels since their discovery has been blamed for this. Annual fossil fuel usage for transportation, energy, and other sectors is projected to be over 15 billion metric tons, resulting in harmful gases that cause severe health im. This has resulted in a significant push for alternative energy sources like wind and solar. Solar is becoming more popular since it is more dependable than wind.. With the rise in solar systems, protection measures are becoming more important than ever. These protection solutions must account for a variety of system components while enhancing redundancy, such as safeguarding the solar panels themselves, storage devices, and loads. This paper provides a feasible protective mechanism for solar-photovoltaic installations operating in island mode. In the conclusion, the findings are analyzed and summarized.